Airline efficiency - Bitzan, John D.; Peoples, James H.; Wilson, Wesley W. (Emerald, 2016)
An efficient air transport system is critical to countries attaining and sustaining healthy economies in an increasingly interconnected world economy. Competing successfully now means quick shipping over long distances at reasonable rates. Societies also prosper when people from different countries can travel around the world using efficient transport. This volume includes literature surveys and original empirical research examining airline efficiency in the twenty first century.Topics cover airline productivity, sources of airline efficiency, the cost and scope of operations in airline transport; airline productivity for different global regions; methodologies estimating productivity growth and efficiency. Further chapters on sources of airline efficiency examine fuel efficiency differences, efficiency in different stages of production, and the contributions of technological change, mergers, and low-cost carrier competition to efficiency. Chapters on the cost and scope of operations examine all-cargo carrier efficiency, gains from airline/high speed-rail cooperation, and airport economies of scope in passenger and freight operations.
Keywords: Airlines -- Management.; elektronické knihy; electronic books